Solenotheres prolixus, a new genus and new species of pinnotherid crab (Crustacea: Decapoda: Brachyura) associated with the razor clam, Solen corneus Lamarck, 1818 (Solenidae) in Vietnam - Ng, Peter K. L.; van Tri, Ngo (Zootaxa, 2010)
A new genus and new species of pinnotherid crab, Solenotheres prolixus, is described from the razor clam, Solen corneus (Solenidae), in Vietnam. The new genus is characterised by its broad and subquadrate carapace, a spatuliform third maxilliped dactylus that is inserted near the base of the propodus, and asymmetrical third ambulatory legs.